Seroprevalence and Risk Factors Associated with Contagious Caprine Pleuropneumonia in Western Amhara, Northwest Ethiopia. (3rd July 2019) - Abrhaley, Askale; Ejo, Mebrat; Fentie, Tsegaw
Abstract : Contagious caprine pleuropneumonia (CCPP) has been identified as a significant problem in goat production, especially in the arid and semiarid lowland areas of Ethiopia. Even though CCPP was reported in most of the goat rearing areas of the country, there is no adequate information on the disease in the Amhara Region. Cross-sectional study was conducted from November 2016 to April 2017 in the districts of Western Amhara to estimate the seroprevalence and identify the associated risk factors for occurrence of the CCPP. The risk factors considered included age, sex, agroclimate, and districts. A competitive enzyme-linked immunosorbent assay (cELISA) was carried out on a total of 400 goat sera samples, out of which 34 samples were found seropositive for specific antibodies against CCPP, with the overall seroprevalence of 8.5% (95% confidence interval (CI) =5.8, 11.2). Among the epidemiological factors considered, age and sex of the goats were not significantly associated with CCPP seroprevalence (p>0.05). However, the seropositivity was slightly higher in adults (9.9%) and female goats (9.0%) compared to young (6.3%) and male (7.5%) goats, respectively. The analysis of seroprevalence by district shows that the seroprevalence of CCPP in Metema (OR=14.34; 95%CI= 1.80, 114.09; p=0.012) and Fogera (OR=9.99; 95%CI= 1.10, 91.16; p= 0.041) was significantly higher compared to other study districts. Multivariable logistic regression analysis also identified the district as a risk factor for the occurrence of a high seroprevalence of CCPP. The present study revealed the seroprevalence and the distribution of CCPP in Western Amhara districts, and hence appropriate control measures including regular investigation and vaccination should be implemented to alleviate the problem.